Adjuvant Transarterial Chemoembolization for Barcelona Clinic Liver Cancer Stage A Hepatocellular Carcinoma After Hepatectomy - Zhang, Yue-Lin; Nie, Chun-Hui; Chen, Feng; Zhou, Tan-Yang; Zhou, Guan-Hui; Zhu, Tong-Yin; Chen, Sheng-Qun; Chen, Xin-Hua; Wang, Hong-Liang; Wang, Bao-Quan; Yu, Zi-Niu; Jing, Li; et al. (Frontiers in Oncology, 2020)
Introduction: The care for patients with hepatocellular carcinoma (HCC) is challenging. This study is to evaluate the effect of adjuvant transarterial chemoembolization (TACE) for Barcelona Clinic Liver Cancer (BCLC) stage A HCC patients after hepatectomy. Methods: Consecutive HCC patients with BCLC stage A, treated by hepatectomy alone (HA) or hepatectomy with TACE (HT), were retrospectively enrolled. Propensity score matching (PSM) was used to balance baseline differences. The recurrence-free survival (RFS) and overall survival (OS) were evaluated using the Kaplan-Meier . The impact of TACE on survival outcome was determined by Cox hazard regression. Results: After PSM, 230 patients (115 HT and 115 HA) were enrolled in the analysis. The 1-, 3-, and 5-year RFS rates were 87.0%, 63.5%, and 50.4% respectivelyfor the HT group, and 87.8%, 67.0%, and 58.3% for the HA group. The OS rates at 1-, 3-, and 5-year were 99.1%, 93.9%, and 87 % respectively for the HT group, and 100%, 92.2%, and 88.7% for the HA group. No significant differences were seen in either the RFS (log-rank test, 2= 0.891, p = 0.345) or OS (log-rank test, 2= 0.146, p = 0.702) between the specific pairs of two groups. Cox regression identified that TACE was not the factor affecting RFS or OS (p = 0.399; HR 0.847; 95%CI 0.576-1.245 for RFS vs. p = 0.989; HR 0.995; 95% CI 0.471-2.100 for OS). Conclusions: Our data indicate that TACE is not an effective intervention in the adjuvant setting for BCLC stage A HCC after hepatectomy.